Exploring the nonlinear impact of critical incidents on customers' general evaluation of hospitality services. (September 2017) - Tontini, Gérson; Bento, Graziela dos Santos; Milbratz, Thaíse Caroline; Volles, Barbara Kobuszewski; Ferrari, Daniela
Abstract: The literature has recognized the existence of a nonlinear impact of service performance on customer satisfaction. Thus, this study investigates use of the critical incident technique as an input to penalty–reward contrast analysis, showing the nonlinear impact of service quality on customers' evaluation of three-star hotels in Rio de Janeiro, Brazil. To do so, it conducts a content analysis of 400 complaints or compliments in online reviews provided by hotel guests, available at www.tripadvisor.com.br. The identified incidents explain 61% (R 2 adj  = 0.61) of the variance in customers' service evaluation. We find that some factors that receive frequent comments on TripAdvisor have low or no impact on customer satisfaction, while others, not frequently reported by customers, have a great impact, which may be either positive or negative. Thus, alongside customers' comments, hotels should explore the nonlinear impact of these comments on customers' general perceptions of service quality.